Granproduktion på tallmarker! : är produktionen hållbar? - Carlsson, Henrik (SLU/Southern Swedish Forest Research Centre, 2003)
The aim of this report was to investigate the hypothesis that Norway spruce (Picea abies L. Karst), planted on poor "Scots pine" stands will not have sustained growth during the whole rotation, due to water deficit in the closed stands. In order to investigate this hypothesis, data from 10 Norway spruce stands in southern-eastern Sweden were collected. In 10 plots in each stand, diameter and breast heights were measured on every tree. Furthermore, height damages and intercept (length of five internodes above 2,5 meters) were measured on sample trees. Totally 2169 trees on 87 plots were measured. Two growth and yield models were used to simulate the growth of the stands. This was done in order to investigate if the height or volume in older stands showed a declined growth when compared to the simulated growth of younger stands. Results from this study did not support the hypothesis of declined growth in mature Norway spruce on poor soils. The simulated growths of the stands were the same as the observed growth of older stands.